Analisis Ergonomi Terhadap Sarana Dan Layout Pada Ruang Kuliah Untuk Kenyamanan Proses Belajar Mengajar Di Program Studi Kesehatan Masyarakat Universitas Muhammadiyah Surakarta - Makhfud, Anas; , Tarwaka, PGDip., Sc., M.Erg; , Rezania Asyfiradayati, SKM., MPH (2017)
Quality teaching and learning process will produce quality learners as well. One that supports it is the good cilities and layout of a lecture room. The purpose of this study is to describe and analyze the ergonomics of facilities and layout in the lecture room for the comfort of teaching and learning process in Public Health Studies Faculty of Health Sciences Universitas Muhammadiyah Surakarta. This research is a descriptive research with evaluation research method. The object in this research is the facilities and layout in lecture room of Public Health Studies Faculty of Health Sciences Universitas Muhammadiyah Surakarta that is lecture room of RD205, RD206 and RD312. Informants in this study are 2 lecturers and 8 students. Data collection in this research is done by literature study, observation and interview. Research results show that the facilities and layout of the lecture room is ergonomic and comfortable for the user. However, there are some things that need to be fixed like a college chair, seat capacity and lighting.